(untitled) - Smits, J. M. (Cheltenham, UK, 2017)
Reflecting the most recent changes in the law, the second edition of this popular textbook provides a fully updated, comparative introduction to the law of contract. Accessible and clear, it is perfectly pitched for international students and courses with a global outlook.
Keywords: Hợp đồng,Contracts; Châu Âu,Europe